Study of Preparation and Thermal Stability of Cyano-Functionalized Imidazolium Type Ionic Liquids - Liang, W.D.; Li, H.F.; Gou, G.J.; Wang, A.Q. (Asian Journal of Chemistry, 2013)
Sixteen imidazolium type cyano-functionalized Brønsted acidic ionic liquids with HSO4– and H2PO4– anion were prepared adopting two-step method and were characterized by FT-IR, 1H and 13C NMR. The onset temperatures of thermal decomposition of the ionic liquids were measured using thermogravimetric analysis. It was found that the decomposition onset temperatures of the as-synthesized ionic liquids were in the range of 200-260 ºC. Additionally, the decomposition temperatures were highly dependent on the nature of the anions. Thermal stability of these cyano-functionalized ionic liquids decreased in the order of HSO4– > H2PO4–.